Radiation Degradation of β-Glucan Extracted from Brewer’s Yeast for Enhancing Growth Promotion and Immunostimulant Activities on Broilers - Nguyen Thanh Long; Tran Le Truc Ha; Hoang Nghia Son; Le Quang Luan (International Journal of Polymer Science)
Water-soluble low molecular weight β-glucan (WSLMG) was successfully prepared via γ-irradiation of insoluble β-glucan extracted from brewer’s yeast cell walls. The WSLMG content in an irradiated sample increased as the irradiation dose increased. The WSLMGs with a molecular weight (Mw) of 49, 25, and 11 kDa, obtained at correlative doses of 100, 200, and 300 kGy, respectively, were tested using growth promotion and immune stimulant effects in broilers. Supplementation with 500 ppm WSLMGs not only increased the survival rate (33.3%) and average body weight (40%) but also reduced the feed conversion rate (35.4%) in tested broilers. In addition, WSLMGs enhanced both nonspecific and specific immune components in the blood of supplemented broilers. The WSLMG with Mw ~25 kDa showed the highest effect on the growth performance and immunomodulatory capability in the immune systems of the tested broilers. In conclusion, this product demonstrates substantial promise as an immunostimulant and growth-promoting additive for poultry.